Oncolytic Viruses in the Treatment of Bladder Cancer - Kyle G. Potts; Mary M. Hitt; Ronald B. Moore (Advances in Urology)
Bladder carcinoma is the second most common malignancy of the urinary tract. Up to 85% of patients with bladder cancer are diagnosed with a tumor that is limited to the bladder mucosa (Ta, T1, and CIS). These stages are commonly termed as non-muscle-invasive bladder cancer (NMIBC). Although the treatment of NMIBC has greatly improved in recent years, there is a need for additional therapies when patients fail bacillus Calmette-Guérin (BCG) and chemotherapeutic agents. We propose that bladder cancer may be an ideal target for oncolytic viruses engineered to selectively replicate in and lyse tumor cells leaving normal cells unharmed. In support of this hypothesis, here we review current treatment strategies for bladder cancer and their shortcomings, as well as recent advancements in oncolytic viral therapy demonstrating encouraging safety profiles and antitumor activity.